Prevalence of type 2 diabetes mellitus and impaired glucose tolerance among ? 30 years of age in an Urban community of Elazig - Özkan, Yusuf; Dönder, Emir; Baydas, Giyasettin; Dogan, Halil; Ilhan, Necip; Açik, Yasemin (My University, 1999)
The present study was undertaken to search the prevalence of Type 2 diabetes mellitus and impaired glucose tolerance (IGT) among ? 30 years of age, to find out the statistical risk factors, and to evaluate the American Diabetes Association's (ADA) criterion for the diagnosis of diabetes mellitus and impaired fasting glucose (EFG) in an urban community of Elazig. Out of 16 public health centres, 8 public health centres were selected in the study. Among the 1255 subject sampled, a total of 958 participants, 572 (60%) women and 386 (40%) men, underwent a standard 75 g OGTT. Type 2 diabetes mellitus and IGT were defined by the World Health Organization's (WHO) criterion and were based on fasting blood glucose and OGTT results. The ADA's criterion for the diagnosis of diabetes was also evaluated. Total cholesterol, LDL, HDL, triglyceride, uric acid, blood pressure, and body mass index were measured. Thirty-nine (4.1%) subjects had previously diagnosed type-2 diabetic and 37 (3.9%) subjects had previously undiagnosed type-2 diabetic. The prevalence of diabetes mellitus was 7.93% and the prevalence of IGT was 12.31%. Total glucose intolerance was 20.24%. IGT was significantly high in women. Among participants, grade 1 obesity was 40.8%, grade 2 obesity was 29%, and grade 3 obesity was 1.4%. Hypertension was significantly high in diabetic people and people who had IGT. According to the ADA criterion, 65 (6.8%) subjects had Type 2 diabetes mellitus and 44 (4.6%) subjects had IFG. Type 2 diabetes mellitus was positively correlated with obesity, hypertension, hyperlipidemia, history of having diabetic family, low physical activity, and age. According to the WHO's criterion, the prevalence of diabetes mellitus was 7.93% and IGT was 12.31% and according to the ADA's criterion, the prevalence of diabetes mellitus was 6.8% and IFG was 4.6% among the subjects ? 30 years of age in an urban community of Elazig. These results were higher than the expected results.
Keywords: Impaired fasting glucose; Impaired glucose tolerance; Type-2 diabetes mellitus; WHO